Multicenter Epidemiologic Study of Coronavirus Disease–Associated Mucormycosis, India - Patel, Atul; Agarwal, Ritesh; Rudramurthy, Shivaprakash M.; Shevkani, Manoj; Xess, Immaculata; Sharma, Ratna; Savio, Jayanthi; Sethuraman, Nandini; Madan, Surabhi; Shastri, Prakash; Thangaraju, Deepak; Marak, Rungmei; et al. (Emerging infectious diseases, 2021)
During September-December 2020, we conducted a multicenter retrospective study across India to evaluate epidemiology and outcomes among cases of coronavirus disease (COVID-19)-associated mucormycosis (CAM). Among 287 mucormycosis patients, 187 (65.2%) had CAM; CAM prevalence was 0.27% among hospitalized COVID-19 patients. We noted a 2.1-fold rise in mucormycosis during the study period compared with September-December 2019. Uncontrolled diabetes mellitus was the most common underlying disease among CAM and non-CAM patients. COVID-19 was the only underlying disease in 32.6% of CAM patients. COVID-19-related hypoxemia and improper glucocorticoid use independently were associated with CAM. The mucormycosis case-fatality rate at 12 weeks was 45.7% but was similar for CAM and non-CAM patients. Age, rhino-orbital-cerebral involvement, and intensive care unit admission were associated with increased mortality rates; sequential antifungal drug treatment improved mucormycosis survival. The COVID-19 pandemic has led to increases in mucormycosis in India, partly from inappropriate glucocorticoid use.